Surfactant Chemistry Effects on Organic Matter Removal from Water Repellent Sand. Issue 5 (20th September 2018) - Song, Enzhan; Goyne, Keith W.; Kremer, Robert J.; Anderson, Stephen H.; Xiong, Xi
Abstract : Core Ideas: Confirmed for the first time that certain wetting agents can remove organic coatings that cause soil hydrophobicity. A novel laboratory experiment was performed to precisely quantify this effect. Possible mechanisms regarding the removal of organic coatings following application of certain wetting agents were discussed. Soil surfactants, which represent a wide range of wetting agent chemistries, have been used as the primary tool for mitigating drought issues caused by soil water repellency (SWR). However, the residual effects of soil surfactants are often short‐lived, requiring repeated applications. Alternatively, certain groups of wetting agents may remove hydrophobic organic matter for extended control of SWR. This laboratory study investigated the effects of selected wetting agent chemistries, including products of alkyl block polymer (ABP), nonionic surfactant + acidifiers (NIS), and polyoxyalkylene polymer (PoAP), for removing organic matter and reducing SWR. Naturally‐occurring hydrophobic sand was packed into sand columns and subjected to wetting agent application. The treated columns were then washed three times with deionized water, and the volume of the leachates from each wash event was determined. Sand treated by PoAP showed enhanced water‐holding capacity, although the effect diminished after the second wash. In comparison, ABP resulted in 2.3‐fold greater output of combined dissolved organic carbon (DOC) and particulate organic carbon (POC) in the leachates than PoAP, and made the hydrophobic sand completely wettable. Alternatively, NIS showed similar effects compared with the control. Although PoAP reduced SWR to a minimum level, it was sorbed strongly to the sand, which resulted in 27% greater solid phase organic carbon (SOC) in treated sand, compared with the untreated control. However, the exact mechanisms underlying surfactant effects on DOC and POC are unclear and the long‐term effects of surfactants following repeated application in the field are yet to be determined.